Seleção de provedores de serviços logísticos utilizando o método de decisão multicritério ahp (analytic hierarchy process): estudo de caso no setor de cargas expressas - Oliveira, Julio Cezar de (2016)
Outsourcing of logistics activities in the Brazil has been growing, allowing companies to direct efforts towards to their core activities and to obtain strategic gains due to the know-how of specialist companies and the possibility of reducing costs with the assets of the contracted company. Thus, tools that aid in the proper selection of suppliers can be important for the company to reach its goals. In this context, the purpose of this study is to apply the Analytic Hierarchy Process (AHP) in the evaluation process and selection of a logistics services providers (LSP) for the courier delivery services company, analyzing qualitative and quantitative criteria that express the real needs of the parties, whose aim is to improve the indicators in terms of quality and customer satisfaction. The results indicated that the information technology, responsiveness and quality of management are the most relevant criteria for the contractor because of the need of preserving the enterprise reliability front of your customers and to remain competitive in the courier delivery services area. The results also showed that the criteria and method used could contribute for classification of LSP suitable for the service in terms of deadline, demand and traceability required for operational success. A sensitivity analysis was also carried out to assess the robustness of the decision. Finally, the proposed model proved to be a good alternative to support the decision on the selection of logistics providers for express charge, since the analysis of qualitative and quantitative criteria adhering to organizational practice, can lead to choosing companies that can meet the quality requirements of the sector.